Down-regulation of the Drosophila morphogen bicoid by the torso receptor-mediated signal transduction cascade. - Ronchi, E.; Treisman, J.; Dostatni, N.; Struhl, G.; Desplan, C. (Cell, 1993)
Anterior body pattern in Drosophila is specified by the graded distribution of the bicoid protein (bcd), which activates subordinate genes in distinct anterior domains. Subsequently, transcription of these target genes is repressed at the anterior pole owing to the activity of the receptor tyrosine kinase torso (tor). We show that both activation by bcd and repression by tor can be reproduced by a minimal promoter containing only bcd-binding sites upstream of a naive transcriptional start site. Repression requires the D-raf kinase and is associated with phosphorylation of bcd protein. Repression does not require either tailless or huckebein, which were previously thought to constitute the sole zygotic output of the tor signaling system. Finally, addition of a heterologous transcriptional activation domain to bcd renders the protein insensitive to tor-mediated repression. We propose that phosphorylation resulting from the activity of the tor signal transduction cascade down-regulates transcriptional activation by the bcd morphogen.